Haiti : Fourth Review Under the Extended Credit Facility: Staff Report and Press Release. (IMF Staff Country Reports; Country Report ;, 2012)
This paper discusses key findings of the Fourth Review Under the Extended Credit Facility (ECF) for Haiti. All end-March 2012 performance criteria were met. Implementation of structural reforms has also continued, although two out of three end-March 2012 structural benchmarks were not observed. The stance of macroeconomic policy and the reform agenda remain broadly unchanged, and will continue to focus on consolidating macroeconomic stability, mobilizing higher revenue to allow increased spending in critical areas and strengthening cash management. Structural reforms will also seek to modernize the financial sector.